2021
DOI: 10.3390/cancers13164168
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Suppresses Tumor Cell-Intrinsic Resistance to Nintedanib and Enhances Its Clinical Activity in Lung Cancer

Abstract: The anti-angiogenic agent nintedanib has been shown to prolong overall and progression-free survival in patients with advanced non-small-cell lung cancer (NSCLC) who progress after first-line platinum-based chemotherapy and second-line immunotherapy. Here, we explored the molecular basis and the clinical benefit of incorporating the STAT3 inhibitor silibinin—a flavonolignan extracted from milk thistle—into nintedanib-based schedules in advanced NSCLC. First, we assessed the nature of the tumoricidal interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Some studies have reported that STAT3 pathway activation may contribute to increase PD-L1, TAP1 and MHC-I levels [39,62,63]. In addition, based on extensive research, the effect of nintedanib on the STAT3 pathway mainly depends on the concentration and cell responsiveness [64][65][66]. Herein, our in vitro results demonstrated that a low concentration of nintedanib (1 μM) can promote STAT3 phosphorylation and downstream protein expression (PD-L1 and β2M) in different tumor cell lines (A549, MC38 and LLC) and gradually suppress these pathways at high doses (5 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that STAT3 pathway activation may contribute to increase PD-L1, TAP1 and MHC-I levels [39,62,63]. In addition, based on extensive research, the effect of nintedanib on the STAT3 pathway mainly depends on the concentration and cell responsiveness [64][65][66]. Herein, our in vitro results demonstrated that a low concentration of nintedanib (1 μM) can promote STAT3 phosphorylation and downstream protein expression (PD-L1 and β2M) in different tumor cell lines (A549, MC38 and LLC) and gradually suppress these pathways at high doses (5 μM).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nintedanib has been suggested to have anti-tumor effects (25,(45)(46)(47)(48) .Researchers now believe that nintedanib's antitumor effect is associated with its ability to inhibit tumor growth in a CD8 + T cell-dependent manner while also inhibiting broblast proliferation and activation (48) .…”
Section: Discussionmentioning
confidence: 99%
“…EMT-driven NSCLC cross-resistance can be abrogated by silibinin, which directly inhibits TGFβR kinase activity and blocks the SMAD signaling cascade in mesenchymal ALK-rearranged NSCLC cells. As EMT is an increasingly recognized driver of innate and acquired resistance to various cytotoxic and targeted drugs, clinically-relevant bioavailable formulations of silibinin with proven anti-cancer activity [ 103 , 104 , 105 ] could be explored as cost-effective and feasible approaches for patients with NSCLC resistant to ALK–TKIs.…”
Section: Discussionmentioning
confidence: 99%